Breeding maize for striga tolerance and the development of a field infestation technique - Kim, S.K. (1991)
Parasitic weed, Striga spp infect million hectares of arable land in Africa and become a major threat to food production in the continent S.hermonthica is a predominant species and causes the highest damage Maize (Zea mays L.) is very susceptible to Striga IITA scientists initiated Striga research on maize in 1982. Resistant sources were discovered in 1983 from IITA inbreds and hybrids which were tested at Mokwa in Nigeria. Most of the resistant materials were originated from the U.S. Corn Belt. Resistant symptoms by Striga infestation on green plant is characterized by less necrotic leaf scorching, less stalk lodging and normal plant growth. Average yield reduction of susceptible maize varieties by Striga was estimated approximately 60%. Grain yield of resistant varieties was highly correlated (r=-617**) with striga rationg Resistance is expressed as tolerance by producing more grain yield under similar level of Striga infestation. The tolerant maize varieties reported have produced 2.5 times more grain yield than the susceptible varieties combining ability studies with ten inbreds to Striga revealed that general combining ability (gca) accounted for 70% for the tolerance and specific combining ability (gca) accounted for 17%. Four lines showed gca effect for tolerance and six lines for susceptibility. Hybridization and recurrent selection could be a powerful breeding techniques to build-up Striga tolerance. Breeding for Striga tolerance or resistance on maize appears to be the most economic way to combat Striga in Africa. Tolerant hybrids developed by IITA maize team grown commercially in Nigeria.